The Effect of E-Service Quality, Website Quality, Promotion, and E-Trust on Repurchase Intentions at E-Commerce Shopee in DKI Jakarta - Muhamad Ilham Syachrony; Hamdan Hamdan; Ridho Rafqi Ilhamalimy (Universitas Muhammadiyah Jakarta, 2023)
This study aims to analyze e-Service Quality, Website Quality, Promotion, and e-Trust against Shopee's Repurchase Intention in DKI Jakarta. This study uses a quantitative approach, and because the population in this study cannot be generalized with certainty, the result is that the sample selection uses a non-probability purposive sampling approach. Obtained 200 samples that have been confirmed as feasible for testing, because they have gone through the data screening stage. The first data analysis uses a descriptive analysis approach to ensure that the sample characteristics are appropriate to the context. Then using PLS-SEM data analysis through Smart-PLS 3.0 Software. The results of this study reveal that e-Service Quality and Website Quality have a negative and insignificant effect on Repurchase Intention. Meanwhile, promotion and e-Trust have a positive and significant effect on Repurchase Intention.